The Role Of Financial Information Quality In Responding To Interest Rate Policy The Central Bank Of Indonesia: Implications For Capital Market Investors - Putri, Rifna Ayu Novita; Fhaeza, Nurul Hilalliyah; Hasan, Nur Anisa (Universitas Negeri Makassar, 2025)
Main objective: This study analyzes the role of financial information quality in helping investors respond to BI interest rate changes, and assesses the contribution of regulations and accounting standards in maintaining information transparency. Method: Using a case study approach on five issuers, it was found that high-quality financial information makes it easier for investors to make decisions when interest rate changes occur. Key Findings: Companies with transparent reporting tend to get a more positive market response. Regulations and reporting standards have also been shown to be important in improving market efficiency by reducing information asymmetry.Keywords:, Financial Information Quality, Interest Rate Policy, Capital Market Investors Tujuan utama: Penelitian ini menganalisis peran kualitas informasi keuangan dalam membantu investor merespons perubahan suku bunga BI, serta menilai kontribusi regulasi dan standar akuntansi dalam menjaga transparansi informasi. Metode: Dengan pendekatan studi kasus pada lima emiten, ditemukan bahwa informasi keuangan yang berkualitas tinggi mempermudah investor dalam mengambil keputusan saat terjadi perubahan suku bunga. Temuan Utama: Perusahaan dengan pelaporan yang transparan cenderung mendapat respons pasar yang lebih positif. Regulasi dan standar pelaporan juga terbukti penting dalam meningkatkan efisiensi pasar dengan mengurangi asimetri informasi. Keywords :, Kualitas Informasi Keuangan, Kebijakan Suku Bunga BI, Investor Pasar Modal